2009
DOI: 10.1016/j.ultsonch.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical preparation of SbSeI gel

Abstract: A novel sonochemical method for direct preparation of nanocrystalline antimony selenoiodide (SbSeI) has been established. The SbSeI gel was synthesized using elemental Sb, Se, and I in the presence of ethanol under ultrasonic irradiation (35 kHz, 2W/cm(2)) at 50 degrees C for 2h. The product was characterized by using techniques such as powder X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), high-resolution transmission electron microscopy (HRTEM), selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…2). During this process the observed SbSeI syneresis was a few times www.intechopen.com larger (Nowak et al, 2009b) than the about 40 % decrease of volume of the dried SbSI ethanogel . It means that the SbSeI ethanogel is much less rigid than the SbSI ethanogel.…”
Section: Sonochemical Preparation Of Photoferroelectric Nanowiresmentioning
confidence: 88%
See 4 more Smart Citations
“…2). During this process the observed SbSeI syneresis was a few times www.intechopen.com larger (Nowak et al, 2009b) than the about 40 % decrease of volume of the dried SbSI ethanogel . It means that the SbSeI ethanogel is much less rigid than the SbSI ethanogel.…”
Section: Sonochemical Preparation Of Photoferroelectric Nanowiresmentioning
confidence: 88%
“…It was found that the SbSI nanocrystals amounts only 4.7 % of volume of the sonicated SbSI xerogel . The surface areas of the sonochemically prepared SbSI and SbSeI were estimated as about 75 m 2 /g and 14÷34 m 2 /g (Nowak et al, 2009b), respectively. Fig.…”
Section: Morphology Composition and Crystal Structure Of Sbsi-type Nmentioning
confidence: 99%
See 3 more Smart Citations